3′ processing in protists - Clayton, Christine; Michaeli, Shulamit (Wiley interdisciplinary reviews. RNA, 2011)
Molecular biologists have traditionally focused on the very small corner of eukaryotic evolution that includes yeast and animals; even plants have been neglected. In this article, we describe the scant information that is available concerning RNA processing in the other four major eukaryotic groups, especially pathogenic protists. We focus mainly on polyadenylation and nuclear processing of stable RNAs. These processes have—where examined—been shown to be conserved, but there are many novel details. We also briefly mention other processing reactions such as splicing. WIREs RNA 2011 2 247-255 DOI: 10.1002/wrna.49 This article is categorized under: RNA Processing > Splicing Mechanisms RNA Processing > 3' End Processing RNA Processing > rRNA Processing
First published: 14 October 2010
Gesehen am 04.04.2022